2D/2D SnO2 nanosheets/Ti3C2Tx MXene nanocomposites for detection of triethylamine at low temperature. Issue 7 (1st April 2022) - Liang, Dong; Song, Peng; Liu, Miao; Wang, Qi
Abstract: Highly active two-dimensional (2D) nanocomposites have been widely concerned in the field of gas sensors because of their unique advantages and synergistic effects. 2D/2D SnO2 nanosheets/Ti3 C2 Tx MXene nanocomposites were synthesized by using layered Ti3 C2 Tx MXene and uniform SnO2 nanosheets by hydrothermal method. Characterization results show that the SnO2 nanosheets are well dispersed and vertically anchored on the layered Ti3 C2 Tx MXene surface, forming heterogeneous interfaces. Based on the gas-adsorption capabilities and synergistic effects of electronic properties, SnO2 nanosheets/Ti3 C2 Tx MXene nanocomposites show high triethylamine (TEA) gas-sensing performance at low temperature (140 °C). The sensor responses of the nanocomposites and pure SnO2 nanosheets to 50 ppm of TEA are 33.9 and 3.4, respectively. An enhancement mechanism for SnO2 nanosheets/Ti3 C2 Tx MXene nanocomposites is proposed for highly sensitive and selective detection of TEA at low temperature. The combination strategy of two-dimensional metal oxide semiconductor and multilayer MXene provides a new way for the development of cryogenic gas sensors in the future.